PENGARUH MANAJEMEN LABA TERHADAP KINERJA KEUANGAN DENGAN TANGGUNG JAWAB SOSIAL PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Perbankan yang Terdaftar di BEI Tahun 2018-2022) - Chofifah, Eichza; Parasetya, Mutiara Tresna (Diponegoro Journal of Accounting, 2024)
This research aims to determine the effect of earnings management on financial performance with corporate social responsibility as a moderating variable. The population of this research is banking sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling method used in this research is a purposive sampling method, so it is known that the research sample consists of 105 companies. The research methods used are classical assumption tests and moderate regression analysis. Based on the results of hypothesis testing, it shows that earnings management has a significant negative effect on return on equity, return on assets and Tobin's Q. Meanwhile, the results of the moderate regression analysis test show that corporate social responsibility moderates the positive and significant effect of earnings management on return on equity, return on assets and Tobin's Q.